2019
DOI: 10.1186/s12888-019-2361-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of schizophrenia and other psychotic disorders among homeless people: a systematic review and meta-analysis

Abstract: BackgroundSchizophrenia and other psychotic disorders constitute a huge global burden of disease and they are major contributors to disability as well as premature mortality among homeless people. This systematic review and meta-analysis aimed to estimate the pooled prevalence of schizophrenia and other psychotic disorders among homeless people.MethodsPubMed, Embase, and Scopus were searched to identify pertinent studies. We used a fixed- or random-effect meta-analysis to pool data from the included studies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 70 publications
3
95
1
1
Order By: Relevance
“…The pooled prevalence of current suicidal ideation among homeless individuals was 17.83% (95% CI: 10.73-28.14) whereas the prevalence of lifetime suicidal ideation was 41.6% (95% CI: 28.55-55.95); the pooled prevalence rates of current and lifetime suicidal attempt were 9.16% (96% CI: 4.1-19.2) and 28.8% (95% CI: 21.66-37.18); no significant difference in the prevalence of lifetime suicidal attempts was found based on the quality of the studies (Ayano, Tesfaw, et al, 2019) Embase, PubMed, Scopus, and additional sources; timeframe was not specified 31; Metaanalysis Studies were conducted in the US (n = 12), Canada (n = 4), Germany (n = 3), two studies Sample size ranged from 33 to 29,143; demographics and recruitment strategy of individual studies were not specified The pooled prevalence of psychotic disorder in homeless people was 21.21% (95% CI: 13.73-31.29); pooled prevalence rates of schizophrenia, schizophreniform disorder, schizoaffective disorder, and psychotic disorder not otherwise specified (NOS) were each in Ethiopia, France, and Scotland; one study each in China, Spain, UK, Ireland, Japan, Serbia, and Australia 10.29% (95% CI: 6.44-16.02), 2.48% (95% CI: 0.16-28.11), 3.53% (95% CI: 1.33-9.05), and 9% (95% CI: 6.92-11.62), respectively. In sensitivity analyses, developing countries had higher prevalence than developed countries (29.16% compared to 18.8% for psychotic disorders, and 22.15% compared to 8.83% for schizophrenia), screening tools revealed higher prevalence than diagnostic instruments (32.19% compared to 17.42%); both for psychotic disorder and schizophrenia, the prevalence rates were higher for studies published on/after 2010 compared to studies published before 2010; no significant difference in prevalence rates was found for the quality of the studies (…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 83%
See 3 more Smart Citations
“…The pooled prevalence of current suicidal ideation among homeless individuals was 17.83% (95% CI: 10.73-28.14) whereas the prevalence of lifetime suicidal ideation was 41.6% (95% CI: 28.55-55.95); the pooled prevalence rates of current and lifetime suicidal attempt were 9.16% (96% CI: 4.1-19.2) and 28.8% (95% CI: 21.66-37.18); no significant difference in the prevalence of lifetime suicidal attempts was found based on the quality of the studies (Ayano, Tesfaw, et al, 2019) Embase, PubMed, Scopus, and additional sources; timeframe was not specified 31; Metaanalysis Studies were conducted in the US (n = 12), Canada (n = 4), Germany (n = 3), two studies Sample size ranged from 33 to 29,143; demographics and recruitment strategy of individual studies were not specified The pooled prevalence of psychotic disorder in homeless people was 21.21% (95% CI: 13.73-31.29); pooled prevalence rates of schizophrenia, schizophreniform disorder, schizoaffective disorder, and psychotic disorder not otherwise specified (NOS) were each in Ethiopia, France, and Scotland; one study each in China, Spain, UK, Ireland, Japan, Serbia, and Australia 10.29% (95% CI: 6.44-16.02), 2.48% (95% CI: 0.16-28.11), 3.53% (95% CI: 1.33-9.05), and 9% (95% CI: 6.92-11.62), respectively. In sensitivity analyses, developing countries had higher prevalence than developed countries (29.16% compared to 18.8% for psychotic disorders, and 22.15% compared to 8.83% for schizophrenia), screening tools revealed higher prevalence than diagnostic instruments (32.19% compared to 17.42%); both for psychotic disorder and schizophrenia, the prevalence rates were higher for studies published on/after 2010 compared to studies published before 2010; no significant difference in prevalence rates was found for the quality of the studies (…”
Section: Characteristics Of the Included Reviewsmentioning
confidence: 83%
“…At the end of this stage, we removed 826 citations due to non-compliance with our criteria and evaluated full texts of the remaining 22 citations. Seven articles were excluded at this stage, and we retained 15 articles in this review (Ayano, Tesfaw, & Shumet, 2019;Ayano, Tsegay, Abraha, & Yohannes, 2019;Bassuk, Richard, & Tsertsvadze, 2015;Burra, Stergiopoulos, & Rourke, 2009;Depp, Vella, Orff, & Twamley, 2015;Duke & Searby, 2019;Embleton, Mwangi, Vreeman, Ayuku, & Braitstein, 2013;Ennis, Roy, & Topolovec-Vranic, 2015;Fazel, Khosla, Doll, & Geddes, 2008;Folsom & Jeste, 2002;Hodgson, Shelton, van den Bree, & Los, 2013;Parks, Stevens, & Spence, 2007;Schreiter et al, 2017;Smartt et al, 2019;Spence, Stevens, & Parks, 2004). The included articles consisted of seven meta-analytic reviews (Ayano, Tesfaw, et al, 2019;Ayano, Tsegay, et al, 2019;Bassuk et al, 2015;Depp et al, 2015;Embleton et al, 2013;Fazel et al, 2008;Schreiter et al, 2017), and eight non-quantitative reviews (Burra et al, 2009;Duke & Searby, 2019;Ennis et al, 2015;Folsom & Jeste, 2002;Hodgson et al, 2013;Parks et al, 2007;Smartt et al, 2019;Spence et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic review and meta-analysis were conducted in adherence to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines [20]. A search was performed in English (PubMed, SZGene) and Chinese (CNKI, Wanfang and Weipu) databases with the following keywords: "the regulator of G-protein signaling 4" or "RGS4" and "schizophrenia".…”
Section: Literature Searchmentioning
confidence: 99%